Oral hygiene, prevalence of gingivitis, and associated risk factors among pregnant women in Sarlahi District, Nepal - D. J. Erchick; B. Rai; N. K. Agrawal; S. K. Khatry; J. Katz; S. C. LeClerq; M. A. Reynolds; L. C. Mullany (BMC, 2019)
Abstract Background The oral health status of pregnant women in low-resource communities such as Nepal has not been well characterized. This sub-population is also of specific interest given associations between poor oral health and adverse pregnancy outcomes previously documented in other settings. We explored relationships between gingivitis and risk factors among pregnant women in rural Nepal. Methods The design was a community-based, cross-sectional study in a sub-area of Sarlahi District, Nepal. Pregnant women < 26 weeks gestation underwent clinical periodontal exams conducted by community-based oral health workers. Exams included a full mouth assessment measuring bleeding on probing (BOP), probing depth (PD) (six sites per tooth), and gingival recession, the distance from the cemento-enamel junction to the free gingival margin (two direct sites per tooth). Data on participant risk factors were collected through household surveys, including demographic characteristics, oral health behaviors, care seeking, and health attitudes. Multivariable logistic regression modeling was used to assess relationships between gingivitis and risk factors. Results We enrolled 1452 participants, of which 40% (n = 582) had signs of clinical gingivitis and 60% (n = 870) clinical health. Average participant age was 23. Most participants (88%) had never received oral health care. Participants averaged 10% of sites with BOP with most (79%) having ≥1 site with BOP. Nine percent of participants had ≥1 site with PD ≥4 mm, although very few participants (0.7%) had sites with PD ≥5 mm. Few participants (13%) had any recession (≥1 mm). In the final adjusted model, odds of gingivitis increased by 3% for each year of age (aOR 1.03, 95% CI 1.00, 1.06) and were higher for women of short maternal stature (< 150 cm) (aOR 1.43, 95% CI: 1.14, 1.79) and among women reporting cost to be a barrier to seeking dental care (aOR 2.13, 95% CI: 1.09, 4.15). Conclusions Gingivitis was common and associated with age, maternal stature, self-reported high cost of dental care, and other risk factors among pregnant women in rural Nepal. Trial registration ClinicalTrials.gov Identifier: NCT01177111 (Nepal Oil Massage Study) and NCT02788786 (Pilot Trial).